A Spectral Approximation of the Barotropic Vorticity Equation (Journal of Computational Mathematics, 1994)
A spectral scheme is considered for solving the barotropic vorticity equation. The error estimates are proved strictly. The technique used in this paper is also useful for other nonlinear problems defined on a spherical surface.